2019
DOI: 10.2340/16501977-2592
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative high-intensity interval training is effective and safe in deconditioned patients with lung cancer: A randomized clinical trial

Abstract: High-intensity interval training is used increasingly in patient care. Various training patterns are used. For patients diagnosed with lung cancer, the first choice intervention is surgery. There is a wait of approximately a mean of 3 weeks between the clinical decision to operate and the intervention. A high-intensity interval training protocol was designed, to be performed during this time-window, to improve the physical condition of these patients before surgery. Patients cycled 3 times per week under super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 36 publications
8
95
0
1
Order By: Relevance
“…For studies that were lacking this information, mean differences were calculated with simple subtraction ("mean_diff" of HIIT -"mean_diff" of UC). The 95% CI of the average difference for Bhatia et al [23] was calculated under the assumption that the data were normally distributed (which is appropriate given the sample size). Other missing standard errors were estimated using the average correlation of two studies: Dunne et al [34] and West et al [35], because these studies used simple between-group comparisons, whereas other studies conducted more complex statistical analyses [17,36], which do not allow for the calculation of the correlation based on the reported summary statistics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For studies that were lacking this information, mean differences were calculated with simple subtraction ("mean_diff" of HIIT -"mean_diff" of UC). The 95% CI of the average difference for Bhatia et al [23] was calculated under the assumption that the data were normally distributed (which is appropriate given the sample size). Other missing standard errors were estimated using the average correlation of two studies: Dunne et al [34] and West et al [35], because these studies used simple between-group comparisons, whereas other studies conducted more complex statistical analyses [17,36], which do not allow for the calculation of the correlation based on the reported summary statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, seven RCTs [15-17, 23, 24, 34, 36] and one non-randomized controlled trial [35] with a total of 896 patients with a mean age of 61 (± 8) years were identified. Seven of the eight studies used a two-arm design (HIIT vs. UC) [16,17,23,24,[34][35][36], whereas one study had a mixed three-arm design comparing HIIT/RT vs. HIIT/MICT vs. UC [15]. No studies were identified that compared HIIT vs. MICT in a prehabilitative setting.…”
Section: Overall Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations